2023
DOI: 10.1049/gtd2.12801
|View full text |Cite
|
Sign up to set email alerts
|

An analytical optimum method for simultaneous integration of PV, wind turbine and BESS to maximize technical benefits

Abstract: The present paper introduces an analytical approach for integrating distributed energy resources (DERs) and battery energy storage systems (BESSs) into power grids. The given method aims to simultaneously identify optimal buses and capacities of DERs and BESSs, with regard to the responsive load demand along with the stochastic nature of wind turbine (WT) and photovoltaic (PV) units, and then to minimize energy losses and improve voltage profiles. For this purpose, the responsive load model, the uncertainties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Studies have shown that wind speed can generally be characterized by Weibull distribution (Khoubseresht et al, 2023), and the Weibull distribution function is given by…”
Section: Distribution Of Wind Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that wind speed can generally be characterized by Weibull distribution (Khoubseresht et al, 2023), and the Weibull distribution function is given by…”
Section: Distribution Of Wind Speedmentioning
confidence: 99%
“…When high winds are accompanied with strong thunderstorms, the risk of the windage yaw flashover under lightning overvoltage increases significantly, and the joint probability distribution of lightning and wind speed should be taken into account in the wind deviation design of the transmission tower so as to ensure the protection effect under the combined meteorological conditions of thunderstorms and high winds. Under the influence of relevance, the statistical characteristics of the joint probability distribution of lightning and wind speed may be significantly different from the univariate distribution (Khoubseresht et al, 2023). Sklar proposed the copula theory, which can decompose the multidimensional joint distribution function into multiple marginal distribution functions and one copula function, and the copula function can describe the relevance characteristics among variables (Henderson et al, 2021).…”
Section: Binary Copula Joint Distribution Functionmentioning
confidence: 99%
“…In [31], an optimal energy scheduling approach for a microgrid with electric vehicles, based on electricity market prices, is proposed to effectively manage the energy flow and charge/discharge of electric vehicles in the microgrid. In [32], an analytical optimization method is proposed for the integration of photovoltaic sources, wind turbines, and energy storage systems to improve microgrid voltage and losses. In [33], the authors have proposed a reinforcement learning (RL) approach for battery scheduling, to optimize user objectives in microgrid energy management.…”
Section: A Background Reviewmentioning
confidence: 99%
“…This is because such coordinated management can absorb intermittency of renewable power generation. Otherwise, the intermittent nature of such energy sources can jeopardize the reliable operation of distribution networks [6]. Also, significant arbitrage benefits can be achieved under dynamic electricity pricing owing to BESS flexibility of dispatching energy at scheduled time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, arbitrage benefits and desired operating strategy of dispatchable sources are the key issues that must be taken care of while solving the decision problem for profit maximization. Nevertheless, the problem is challenging on account of dynamic behaviour of the generation from RESs, demand, and electricity market that lead to a complex process which needs adaptive strategies to deal with BESSs [6]. The consideration of dynamic electricity price may further add computational burden to the optimization technique on account of dynamically varying system states with large number of state variables [7].…”
Section: Introductionmentioning
confidence: 99%